2021
DOI: 10.3390/foods10092081
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri FYNLJ109L1 Attenuating Metabolic Syndrome in Mice via Gut Microbiota Modulation and Alleviating Inflammation

Abstract: Metabolic syndrome is caused by an excessive energy intake in a long-term, high-fat and/or high-sugar diet, resulting in obesity and a series of related complications, which has become a global health concern. Probiotics intervention can regulate the gut microbiota and relieve the systemic and chronic low-grade inflammation, which is an alternative to relieving metabolic syndrome. The aim of this work was to explore the alleviation of two different Lactobacillusreuteri strains on metabolic syndrome. Between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Escherichia-Shigella, Enterococcus, Clostridium_sensu_stricto_1, Erysipelatoclostridium, Colidextribacter and Akkermansia were increased in the fDKO-WT group compared to in the fDWT-WT group. Escherichia-Shigella and Enterococcus are potential pathogens [55,56], and studies found that Clostridium_sensu_stricto_1, Erysipelatoclostridium and Colidextribacter were increased in high-fat diet-fed mice [43,44,57]. Similar to our results, Xu et al found that the relative abundance of Akkermansia was markedly increased after chronic DSS induction [50].…”
Section: Effect Of Lf Feeding De Ciency During Lactation On Gut Micro...supporting
confidence: 88%
“…Escherichia-Shigella, Enterococcus, Clostridium_sensu_stricto_1, Erysipelatoclostridium, Colidextribacter and Akkermansia were increased in the fDKO-WT group compared to in the fDWT-WT group. Escherichia-Shigella and Enterococcus are potential pathogens [55,56], and studies found that Clostridium_sensu_stricto_1, Erysipelatoclostridium and Colidextribacter were increased in high-fat diet-fed mice [43,44,57]. Similar to our results, Xu et al found that the relative abundance of Akkermansia was markedly increased after chronic DSS induction [50].…”
Section: Effect Of Lf Feeding De Ciency During Lactation On Gut Micro...supporting
confidence: 88%
“…Escherichia-Shigella, Enterococcus, Clostridium_sensu_stricto_1, Erysipelatoclostridium, Colidextribacter and Akkermansia were increased in the fDKO-WT group compared to in the fDWT-WT group. Escherichia-Shigella and Enterococcus are potential pathogens [55,56], and studies found that Clostridium_sensu_stricto_1, Erysipelatoclostridium and Colidextribacter were increased in high-fat diet-fed mice [43,44,57]. Similar to our results, Xu et al found that the relative abundance of Akkermansia was markedly increased after chronic DSS induction [50].…”
Section: Effect Of Lf Feeding De Ciency During Lactation On Gut Micro...supporting
confidence: 87%
“…For identifying significantly different species across groups, the LDA score was used in our study (Figure 6). L. reuteri and B. pseudolongum were considerably different in the Rnls +/+ -ND group, and both have been described as probiotics in previous studies [41][42][43]. S24-7 and Lactobacillus were considerably different in the Rnls −/− -ND group, and both have been reported by decreasing the risk of obesity [44].…”
Section: Discussionmentioning
confidence: 67%